KORELASI PENGETAHUAN LINGKUNGAN DENGAN UPAYA MITIGASI PERUBAHAN IKLIM DI SEKTOR TRANSPORTASI PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT - najmi putri naifah; Sri Malem Indirawati (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Background: Air pollution is currently dominated by the transportation sector, which is the second-largest contributor after the energy sector in Indonesia. Its impacts not only damage the environment but also pose serious health risks. As an educated group, students need to take mitigation actions. This study aims to analyze the correlation between environmental knowledge and climate change mitigation efforts in the transportation sector among students of the Faculty of Public Health, Universitas Sumatera Utara. Method: This research used an analytical survey design. The population consisted of 1,403 undergraduate students from the 2021–2024 cohorts, with a sample of 93 respondents determined using the Slovin formula and selected through accidental sampling. The inclusion criteria were students who owned private transportation. Data were collected through questionnaires and analyzed using univariate and bivariate methods. Results: Most respondents were female (87.1%) and aged 20–22 years (68.8%), with monthly allowances ranging from Rp500,000 to Rp5,000,000. Motorcycles were the most common mode of transport (83.9%), used 5–6 days per week (71%), with 73.1% using Pertalite fuel. The average weekly travel distance was 78.494 km, with fuel consumption of 7.819 liters and a cost of Rp105,903.23. The mean annual CO₂ emission was 0.74784 tons, ranging from 0.038 to 2.89 tons. Students demonstrated good knowledge (87.1%) and attitudes (89.2%), but mitigation actions remained low (57%). Conclusion: Public Health students at Universitas Sumatera Utara possess good knowledge and attitudes toward climate change mitigation, yet their practical actions remain limited, such as not turning off vehicle engines when idling.